Simultaneous estimation of parabens and bisphenol a in ready-to-eat foodstuffs by using QbD-driven high-pressure liquid chromatography method. Issue 10 (9th August 2022) - Pradhan, Rajesh; Hejmady, Siddhanth; Taliyan, Rajeev; Khadgawat, Rajesh; Gupta, Tarang; Kachhawa, Garima; Kumar, Rajesh; Singhvi, Gautam; Kumar Dubey, Sunil
ABSTRACT: Endocrine-disrupting chemicals (EDC) are harmful xenobiotics show casingv aried unwanted effects altering the endocrine system and its functions. Exposure of EDCs to humans occurs through route sincluding air, water, skinand via contaminated food. The food stuffs primarily used in daily activities contain preservatives and plasticisers. Parabens are routinely used as preservatives in foods, beverages, and pharmaceuticals whereas bisphenol A (BPA) is utilised in food cans, beverage bottles and polycarbonate tableware. In this research work, we have developed a sensitive high-performance liquid chromatography (HPLC) based method and validated it to simultaneously estimate methylparaben (MP), ethylparaben (EP), propylparaben (PP) and BPA with a linearity range of 25–1600 ng/mL utilising QbD approach. The developed method was validated for linearity, accuracy, precision, sensitivity, and robustness according to the International Conference on Harmonisation (ICH) guidelines. Estimation of EDCs in ready-to-eat (RTE) food materials was undertaken by the application of this validated method. The results showed significant amounts of EDCs in RTE samples. Thus this preliminary study investigated the presence of MP, EP, PP, and BPA in these foodstuffs to raise awareness amongst researchers as well as governing bodies regarding food contamination.